Informal relationships at workplace and employee performance: A study of employees private higher education sector - Zahra Amjad; Pirzada Sami Ullah Sabri; Muhammad Ilyas; Afshaan Hameed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Now a day's employees spend a large portion of their lives at workplace. Accordingly, friendships among employees are often formed at work place. The objective of this study was to determine the impact of workplace friendship (WPF) on employee task and contextual performance, job satisfaction (JS) and turnover intentions (TI) in university employees of higher education institutes of Punjab, Pakistan. In addition the study aimed at investigating what extent job satisfaction mediates the relationship among workplace friendship, TI, Task performance (TP), and contextual performance (CP). Data were collected from 500 teachers of private sector higher education Institutes of Punjab. Step wise Regression analyses and Principal Component analysis were used to confirm the research hypothesis. Results showed two things: first the workplace friendship has variety of positive functions for individual performance and job satisfaction positively and significantly mediates between the relationships of TI, CP, TP, and workplace friendship. Second work place friendship moderates the relationship between organization commitment and turnover intentions. The focus of the research was the employees of private sector HEIs only. Since the participants were only from the five private sector universities so the findings cannot be generalized to the employees of public sector universities. Considering the importance of employee's performance, workplace friendship and organizational commitment in Higher Education Institution (HEIs) researchers, policy makers and academic administrative should take necessary measures to increase the satisfaction and commitment of the employees through informal relations. Further this makes the valuable contribution to both work place friendship and turnover intentions literature by being one of the mediating and moderator effects.
Keywords: 330; workplace friendship; turnover intentions; contextual performance; task performance; organizational commitment; higher education institutes